2009
DOI: 10.1097/ccm.0b013e3181b0266c
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of a phospholipid emulsion (GR270773) in Gram-negative severe sepsis: Results of a phase II multicenter, randomized, placebo-controlled, dose-finding clinical trial

Abstract: Treatment with phospholipid emulsion did not reduce 28-day all-cause mortality, or reduce the onset of new organ failure in patients with suspected or confirmed Gram-negative severe sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 25 publications
1
28
1
1
Order By: Relevance
“…Generally speaking, endotoxin is present in many critically ill patients without the criteria of sepsis [3]. To date, studies neutralizing the effects of endotoxin activity have not shown any benefit, the latest being the phospholipid study [21] and the inhibitor of Toll-like receptor-4-mediated signaling study [22]. It may well be that total neutralization of endotoxin is deleterious.…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, endotoxin is present in many critically ill patients without the criteria of sepsis [3]. To date, studies neutralizing the effects of endotoxin activity have not shown any benefit, the latest being the phospholipid study [21] and the inhibitor of Toll-like receptor-4-mediated signaling study [22]. It may well be that total neutralization of endotoxin is deleterious.…”
Section: Discussionmentioning
confidence: 99%
“…However, several large follow-up randomized controlled trials with both HA-1A as well as E5 were negative and neither drug was approved for clinical use in the United States [12,13]. More recently, additional attempts at neutralizing endotoxin to increase survival in severe sepsis utilizing (a) bactericidal/permeability-increasing protein, (b) a lipid emulsion of recombinant HDL that binds endotoxin, (c) a small molecule TLR4 inhibitor (TAK242), and (d) E5564, a lipid A analogue and competitive inhibitor of TLR4, also all failed to show reduction in mortality in severe sepsis patients [14-16]. …”
Section: Introductionmentioning
confidence: 99%
“…This effect has been shown previously in a study of normal human volunteers receiving an intravenous dose of Escherichia coli endotoxin during a 6-h PL infusion, and attenuation of the clinical and laboratory responses were directly related to PL levels in the bloodstream [39]. However, when this formulation was tested in the critical care setting in patients with severe Gram-negative sepsis, the high dose arm (1350 mg/kg by continuous infusion) had to be stopped because of the increased incidence of life-threatening significant adverse events and obvious futilty to show a survival advantage [40]. The PL emulsion used in this investigation consisted of 92.5% soy-based, PL, and 7.5% soy triglycerides.…”
Section: Discussionmentioning
confidence: 99%